On Symmetric Identities of Carlitz’s Type q-Daehee Polynomials - Won Joo Kim; Lee-Chae Jang; Byung Moon Kim (Discrete Dynamics in Nature and Society)
In this paper, we study Carlitz’s type q-Daehee polynomials and investigate the symmetric identities for them by using the p-adic q-integral on Zp under the symmetry group of degree n.